Perception of Diabetic Patients Toward the Risk of Diabetic Foot Ulcers - Sri Mulyati Rahayu Rahayu; Vina Vitniawati; Ali Hamzah (Sarana Ilmu Indonesia (salnesia), 2026)
The increasing prevalence of Diabetes Mellitus in Indonesia raises concerns about long-term complications such as diabetic foot ulcers, which can lead to amputation, disability, and reduced productivity and quality of life. Despite the availability of health education and promotive-preventive services, 79.1% of Diabetes Mellitus patients have poor foot care practices. Therefore, this study aimed to analyze Diabetes Mellitus patients' perceptions of the risk of diabetic foot ulcers. The method used was descriptive phenomenological, through in-depth interviews and focus group discussions. The sampling technique used purposive sampling until data saturation was achieved. The sample size was 15 DM patients, and the research locations were Riung Bandung Community Health Center and Bandung City Hospital. Data were analyzed using the Colaizzi method. The results showed a negative emotional response at the initial diagnosis that developed into acceptance through family and spiritual support. The perception of diabetic foot ulcers was the most frightening, affecting independence. Preventive behavior was influenced by knowledge, experience, fear of amputation, and access to education. In conclusion, patients perceive diabetic foot ulcers as dangerous, difficult to heal, at risk of infection, and even leading to amputation. Patients' recommendations call for concrete, empathetic, interactive, and ongoing education from healthcare professionals.